Penerapan Intervensi Manajemen Halusinasi terhadap Tingkat Agitasi pada Pasien Skizofrenia - Fitri Wijayati; Nurfantri Nurfantri; Gita Putu Chanitya Devi (Poltekkes Kemenkes Kendari, 2019)
Schizophrenia is a condition in which a person experiences a significant change in behavior, someone who experiences this disorder becomes self-forgetful, behaves abnormally, injures himself, shuts himself in, does not want to socialize, lacks self-confidence and often enters the subconscious in a full fantasy world. delusions and hallucinations. This case study research uses a descriptive research design aimed at implementing hallucination management interventions on the level of agitation in patients with auditory hallucinations The sample in this study were schizophrenic patients who experienced cooperative auditory hallucinations. The results and conclusions of this study were that there was an effect of giving speech therapy. with others to levels of agitation, restlessness and insomnia. In the nine days of intervention, for the level of agitation agitation showed a scale of 4 categories of mild and for the level of agitation insomnia showed a scale of 3 categories of moderate. Suggestions are expected that further researchers can use it as a guide in implementing hallucination management in schizophrenia patients.